Peran ASEAN dalam Menghadapi Isu Pelanggaran HAM Pasca Kudeta Militer di Myanmar Tahun 2021 - Oktaviani, Jusmalia; Riva, Lusian (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2022)
The background of this research The background of this research is the military coup in Myanmar in 2021, military coup occurred because of allegations of corruption and election fraud Myanmar in 2020 won by National League for Democracy. Myanmar’s people refuse the coup by doing a demonstration to government and new policies, but Tatmadaw reactionto rejection of the coup resulted a human Rights violations, many victims were killed, violence against society, and violate individual rights. This case raises the issue of human rights violations was conducted by Myanmar post military coup, ASEAN as regional organization in Southeast Asia have the authority to give a response on the issue of human rights violations in Myanmar post military coup. This research used qualitative-descriptive method with liberalism institutionalism and role of international organizations, in this research was conducted to describe the role of ASEAN in resolve the issue of human rights violations in Myanmar post military coup. The result of this research show ASEAN’s role as a communication and cooperation tool to raise this issue in ASEAN’s forum, ASEAN as a platform to generate of five point consensus as a positive solution for Myanmar, and ASEAN as administration platform in promoting realization of five point consensus. All forms of ASEAN’s action in 2021 until 2022 is a part of ASEAN effort to resolve human rights violations in Myanmar post military coup.